Aplikasi Sensor BH1750 Untuk Sistem Monitoring Pertumbuhan Tanaman Cabai Menggunakan Arduino Bertenaga Surya Terintegrasi Internet of Things (IoT) - Wahyu, Syafrima; Syafaat, Mohamad; Yuliana, Agnes; Meliyani, Revi (Jurnal Teori dan Aplikasi Fisika, 2021)
The purpose of this study is to design the monitoring system to observe the growth of Chili plant that is integrated with the Internet of Things (IoT) with the power source coming from solar panels. Important variables to support plant growth are soil moisture, ambient temperature as well as the right time and duration of watering. Measurement of light intensity is carried out by the BH1750 sensor. The measurement results of the sensor will be displayed on the LCD (Liquid Crystal Display) and can be accessed via an Android-based application. The result of testing the light intensity monitoring tools on chili plants showed good accuracy. The monitoring system that has been designed is equipped LCD that show variable result.